Towards an understanding of Li-Fi: Next generation Visible Light Communication Technology (International Journal of Engineering and Computer Science, 2017)
Li-Fi (Light Fidelity) is an optical version of Wi-Fi (Wireless Fidelity) technology. This technology is based upon the concept of visible light communication (instead of radio frequency waves). This technology introduced by German Physicist Harald Hass, the idea is to communicate through illumination i.e. use of LED light bulbs for data transmission. This paper gives an overview and working principle of the technology including its advantages, disadvantages and applications. Further the Li-Fi is compared to other existing communication technologies and the scope of Li-Fi in existing connectivity scenario is discussed.